ESTIMATING THE RELATIONSHIP BETWEEN GOVERNANCE, ECONOMIC GROWTH, INEQUALITY AND POVERTY - TOUITOU, Mohammed (Theoretical and Practical Research in Economic Fields; Vol 12 No 1 (2021): TPREF, Volume XII, Issue 1(23), Summer 2021, 2021)
The main purpose of this paper is to estimate the relationship between governance, economic growth, inequality and poverty for 81 countries for the period 2000-2016. We divided the countries into three groups, low-income countries, lower-middle-income countries and upper-middle-income countries. To answer our research question, we use a structural model with simultaneous equations on Panel data. Our results show that the positive or negative impact of governance on the growth-inequality-poverty triangle changes depending on the dimension of governance taken into account and the sample being studied. Given the negative relationship between inequality and growth, democracy should a second time positively affect economic growth through the reduction of inequalities.